Positron Emission Tomography Imaging of the Serotonin Transporter and 5-HT1A Receptor in Alcohol Dependence - Martinez, Diana; Slifstein, Mark; Gil, Roberto; Hwang, Dah-Ren; Huang, Yiyun; Perez, Audrey; Frankle, W. Gordon; Laruelle, Marc; Krystal, John; Abi-Dargham, Anissa (Biological psychiatry (1969), 2009)
Background Rodent models as well as studies in humans have suggested alterations in serotonin (5-HT) innervation and transmission in early-onset genetically determined or type II alcoholism. This study examines two indices of serotonergic transmission, 5-HT transporter levels and 5-HT1A availability, in vivo, in type II alcoholism. This is the first report of combined tracers for pre- and postsynaptic serotonergic transmission in the same alcoholic subjects and the first study of 5-HT1A receptors in alcoholism. Methods Fourteen alcohol-dependent subjects were scanned (11 with both tracers, 1 with [11 C]DASB only, and two with [11 C]WAY100635 only). Twelve healthy control subjects (HC) subjects were scanned with [11 C]DASB, and another 13 were scanned with [11 C]WAY100635. Binding potential (BPp , mL/cm3 ) and the specific to nonspecific partition coefficient (BPND , unitless) were derived for both tracers using a two-tissue compartment model and compared with control subjects across different brain regions. Relationships to severity of alcoholism were assessed. Results No significant differences were observed in regional BPp or BPND between patients and control subjects in any of the regions examined. No significant relationships were observed between regional 5-HT transporter availability, 5-HT1A availability, and disease severity, with the exception of a significant negative correlation between 5-HT transporters and years of dependence in amygdala and insula. Conclusion This study did not find alterations in measures of 5-HT1A or 5-HT transporter levels in patients with type II alcoholism.